Modified cellulose aerogel as well as preparation method and application thereof
Through the combination of modified cellulose aerogel and Ti3C2Tx/ZIF-8 materials, the problem of traditional air filtration equipment failure in high temperature and high humidity environments is solved, and a self-powered air filtration equipment with high efficiency filtration and quick response is achieved, with excellent stability and reusability.
Patent Information
- Application Number
- CN202411490579.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-24
AI Technical Summary
Traditional air filtration equipment fails in high temperature and high humidity environments, affecting the stability of self-powered medical equipment. Moreover, the filtration performance of petroleum-based materials is severely degraded after repeated use, making it difficult to recycle.
Modified cellulose aerogel is used as the cathode material of triboelectric nanogenerator. By combining with Ti3C2Tx/ZIF-8 material, the spinnability and hydrophilicity of cellulose are enhanced, and the cellulose is modified by silane grafting to improve Its stability in high temperature environments.
It achieves high-efficiency filtration of PM0.3, PM0.5 and PM1, maintains high filtration efficiency after 7 cleanings, has a 99.9% sterilization rate and the ability to quickly respond to NH3, significantly improving electrical output performance and reducing energy consumption.
Smart Images

Figure CN119350700A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano energy, and specifically relates to a modified cellulose aerogel and a preparation method and application thereof. Background Art
[0002] High concentrations of particulate matter (PM) and toxic gas compounds produced by combustion in fire accidents pose a serious threat to human health and life. In addition, particulate matter has a large surface area and stays in the air for a long time, which can effectively promote the long-distance and long-term transmission of viruses, bacteria and toxic substances, thereby exacerbating health risks.
[0003] Conventional air filtration devices achieve high filtration efficiency at the expense of increased pressure drop, which greatly increases energy consumption. In addition, electronic filtration devices often fail at high temperatures and pose safety risks such as power supply explosion. Therefore, self-powered air filtration devices have become a prominent research focus. Triboelectric nanogenerators (TENGs) have shown great potential as efficient electromechanical conversion devices in self-powered healthcare devices. Driven by respiration, TENGs generate an induced electric field that polarizes inhalable particles and effectively adsorbs them on the surface of the material.
[0004] Ammonia (NH3) is different from common gases such as CO2 and is usually not present in the daily environment. Therefore, NH3 monitoring is a reliable indicator of toxic gas leakage or generation in fires. MXene is a new type of two-dimensional transition metal material. Due to its excellent conductivity, high selectivity for NH3 and abundant active sites, it has attracted widespread attention in self-powered sensing, energy storage and catalysis. As a highly efficient electromechanical conversion device for self-powered air filtration, TENGs have shown great potential. However, the complex environment of high temperature and high humidity in fire accidents can cause charge dissipation or neutralization, thereby reducing the output performance of TENGs and affecting the stability of self-powered medical devices based on TENGs. Due to the difficulty in recycling petroleum-based medical devices and the prevalence of the concept of sustainable development, the development of biomass materials has become a hot research topic. Among them, cellulose has attracted the interest of many researchers due to its wide source in nature, sustainability and degradability. However, the poor spinnability and hydrophilicity of cellulose limit its development as a self-powered air filtration material. In addition, the filtration performance of petroleum-based medical devices will be severely degraded after repeated use, further exacerbating the exploitation of petroleum resources. Summary of the invention
[0005] In order to solve the above-mentioned technical problems, this application provides the following technical solutions: The present invention provides a method for preparing a modified cellulose aerogel, comprising the following steps: S11: adding a cellulose compound to a silane hydrolyzate and heating and mixing the mixture, and dispersing the separated solid in an aqueous solution of lithium bromide to obtain a mixed dispersion; the silane hydrolyzate is obtained by heating and mixing tetraethyl orthosilicate, ammonia water and ethanol at 50-75° C. for 8-20 h; S12: Add Ti3C2T x / ZIF-8 material, after mixing, heating and reacting, cooling to obtain a hydrogel; the Ti3C2T x / ZIF-8 material was obtained by mixing solution B and solution A and reacting them at room temperature (25±5℃) for 12-48 h; The solution A is obtained by mixing methanol containing dimethyl imidazole and zinc nitrate; the solution B is obtained by mixing Ti3C2T x (CAS No. 12363-89-2) is added to methanol containing zinc nitrate; S13: washing the hydrogel, freeze-drying it, and heat-treating it to obtain the modified cellulose aerogel.
[0006] ZIF-8 was in situ polymerized onto Ti3C2Tx to synthesize Ti3C2Tx / ZIF-8. Silane was hydrolyzed at room temperature and then added to a solution containing cellulose and lithium bromide. Silane was grafted onto the cellulose surface to prepare a cellulose mixed solution. Ti3C2Tx / ZIF-8 was then grafted onto the cellulose surface via silane. Cellulose was heated at high temperature until it dissolved, then cooled to room temperature to form a cellulose hydrogel. After washing, cellulose aerogel was obtained by freeze drying. Then, heat treatment was performed to obtain a cellulose-based aerogel.
[0007] This method has the advantages of easy availability of raw materials, simple process and superior performance.
[0008] Specifically, the Ti3C2T x The preparation method of / ZIF-8 is as follows: 0.1-1mmol zinc nitrate (Zn(NO3)2) is pre-added as a crystal growth seed in 20-90mL methanol solution containing dimethylimidazole (2-M) (0.01-0.5 mol / L) to obtain a mixed solution A; Ti3C2T x Immerse in 20-90 mL Zn(NO3)2 methanol (0.01-0.1 mol / L) for 0.5-6 hours to obtain solution B, then mix the mixture of solution B into the mixture of A and solution B, stir slightly, and react at room temperature for 12-48 hours.
[0009] Preferably, the cellulose compound is selected from microcrystalline cellulose, nanocellulose or cellulose; and the mass ratio of the cellulose compound to the silane hydrolyzate is 1:5-15.
[0010] Preferably, in step S11, the cellulose compound and the silane hydrolyzate are heated and mixed at a temperature of 50-70° C. for 5-24 h.
[0011] Preferably, in the aqueous solution of lithium bromide, the weight ratio of lithium bromide to water is 2:1-3, and the solution is stirred at 0-15°C for 0.5-5 h.
[0012] Preferably, in step S11, the separation method is vacuum filtration, and the dispersion method is stirring at room temperature for 0.5-2 h, and then ultrasonic dispersion for 0.5-2 h.
[0013] Preferably, in the mixed dispersion, the mass concentration of the cellulose compound is 0.1-3%.
[0014] Preferably, in the silane hydrolyzate, the volume ratio of tetraethyl orthosilicate, ammonia water and ethanol is 0.8-1.4:9-14:92-108.
[0015] Preferably, in step S12, Ti3C2T x The mass ratio of the cellulose compound in the / ZIF-8 material and the mixed dispersion is 0.02-0.3:0.8-1.2.
[0016] Preferably, in step S12, the dispersion and Ti3C2T x The method for mixing the ZIF-8 material is to stir at room temperature for 0.5-3 h and then disperse by ultrasonic for 0.5-1 h.
[0017] Preferably, in step S12, the heating reaction temperature is 95-140° C., the time is 1-10 min, and the cooling is 6-24 h.
[0018] Preferably, in the methanol containing dimethylimidazole, the concentration of dimethylimidazole is 0.01-0.5 mol / L.
[0019] Preferably, in step S13, the cleaning method is to wash the hydrogel with water, ethanol and tert-butanol in sequence, each washing for 0.5-2 h, and then replace the solution and wash for 24 h.
[0020] Preferably, in step S13, the heat treatment method is: heating the freeze-dried hydrogel at 150-200° C. for 0.5-4 h, and then heating at 220-260° C. for 0.5-4 h under a protective atmosphere.
[0021] Furthermore, the protective atmosphere is selected from nitrogen or argon.
[0022] The present invention also provides a modified cellulose aerogel prepared by the above preparation method.
[0023] The present invention also provides a friction nanogenerator, which uses the modified cellulose aerogel as a positive electrode material.
[0024] The modified cellulose aerogel of the present invention can be used together with the electrospinning film of polyvinylidene fluoride and nano-barium titanate as the positive and negative triboelectric materials of the friction nanogenerator, respectively. The friction nanogenerator based on cellulose aerogel is suitable for many fields such as efficient air filtration, rapid sterilization, rapid response to ammonia concentration, repeated use and monitoring of respiratory health.
[0025] The technical solution of the present invention has the following advantages over the prior art: (1) The present invention endows cellulose aerogel with strong electron loss ability, making it a strong triboelectric positive electrode material that can replace animal hair, polyimide and nylon. After being assembled with the negative electrode material, the voltage is as high as 130 V. Thanks to the dual effects of physical interception and electrostatic adsorption, it is very effective in PM 0.3 、PM 0.5 The filtration efficiency of PM2.5 and PM1 exceeded 99.2%. After 7 cleanings, the filtration efficiency of PM 0.3 The filtration efficiency is still over 89%.
[0026] (2) The cellulose aerogel in the present invention can achieve a 99.9% sterilization rate after 20 minutes under near-infrared light irradiation. After seven washes, the antibacterial rate is still over 97%.
[0027] (3) It can accurately detect 1 ppm NH3 and respond quickly. The response rate to 100 ppm NH3 is 78% within 12 seconds, which can quickly warn of NH3 leakage.
[0028] (4) The process flow designed by the present invention is short, the equipment is simple, and the cost is low. It can significantly improve the electrical output performance and has wide applications in energy collection, human health monitoring, air purification, and intelligent sensing. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 (a) Raman spectrum and (b) XRD pattern of the material.
[0030] Figure 2 Figure 1 is a graph of filtration efficiency at 95% relative humidity.
[0031] Figure 3 This is a test chart of the antibacterial rate and ammonia response stability of modified cellulose aerogel after different irradiation times. DETAILED DESCRIPTION
[0032] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention. Example 1
[0033] (1) Preparation of modified cellulose aerogel 0.4 mmol Zn(NO3)2 was pre-added as a seed for crystal growth in 40 mL of 2-M (0.1 mol / L) methanol solution to obtain a mixed solution A. Ti3C2T x Soak in 30mL Zn(NO3)2 methanol (0.22 mol / L) for 1.5 hours to obtain solution B, then mix the mixture of solution B into the mixture of A and solution B, stir slightly, and react at room temperature for 20 hours. The silane hydrolyzate is composed of tetraethyl orthosilicate, ammonia water and ethanol in a volume ratio of 1:10:95, and is stirred at 50°C for 10 hours. The weight ratio of anhydrous lithium bromide to water is 2:1, and it is stirred at 5°C for 2 hours. Add microcrystalline cellulose to the silane hydrolyzate in a mass ratio of 1:10 and stir at 70°C for 20 hours. The cellulose grafted with silane is filtered out by vacuum and placed in a pressure-resistant bottle containing lithium bromide solution, with cellulose accounting for 0.5% of the total weight of the solution. Stir at room temperature for 1 hour, then ultrasonically disperse for 0.5 hours. Then add Ti3C2T x / ZIF-8, Ti3C2T x The weight ratio of / ZIF-8 to cellulose was 0.05:1.02, stirred at room temperature for 1 h, and then ultrasonically dispersed for 0.5 h. The cellulose solution was heated to 110 ° C for 2 min, then poured into a petri dish and cooled for 12 h to obtain a hydrogel. The hydrogel was then washed with water, ethanol, and tert-butanol in sequence, each washing for 1 h, and then the solution was replaced and washed for 24 h. The cellulose aerogel was obtained after freeze-drying. It was then placed in a nitrogen or argon environment and heated at 150 ° C for 2 h, and then heated at 220 ° C for 0.5 h.
[0034] (2) Preparation of triboelectric nanogenerator The modified cellulose aerogel prepared above was selected as the positive electrode of the friction nanogenerator, and the nanofiber membrane of polyvinylidene fluoride and nano-barium titanate was used as the negative electrode, with a size of 4π cm 2 , copper foil was covered on the back of the two triboelectric materials, and then fixed on acrylic plates, and the wires were connected to the upper and lower electrodes. The contact separation power generation test of the triboelectric nanogenerator was carried out with a pressure of 10N and a frequency of 4Hz.
[0035] (3) The open circuit voltage of the positive electrode of the triboelectric nanogenerator using pure cellulose nanofiber membrane without any modified materials is 58V; the open circuit voltage of the triboelectric nanogenerator using the modified cellulose-based aerogel of this embodiment as a triboelectric nanogenerator is 110V. It can be seen that the electrical output performance of the triboelectric nanogenerator of this embodiment is significantly improved. 0.3 、PM 0.5 The filtration efficiency of PM2.5, PM3 and PM4 reached 98.08%, 98.59% and 99.02% respectively. Even under the harsh conditions of 95%RH and high humidity, the filtration efficiency can be maintained above 89%. After 7 cycles of "test-washing", the filtration efficiency of PM2.5 was 1.34%. 0.3 The filtration performance is still over 92%. After 20 minutes of near-infrared light irradiation, the antibacterial rate of Escherichia coli and Staphylococcus aureus reached 99.1%. The device can accurately detect 5ppm of NH3 and respond quickly, with a response rate of 72% to 100ppm of NH3 within 13 seconds. Even after 8 cycles of "test-washing", the bactericidal property and ammonia responsiveness remain extremely stable. By monitoring the wearer's breathing status in real time, respiratory health status can be continuously assessed. Example 2
[0036] (1) Preparation of modified cellulose aerogel 0.5 mmol Zn(NO3)2 was pre-added as a seed for crystal growth in 50 mL of 2-M (0.4 mol / L) methanol solution to obtain a mixed solution A. Ti3C2T x Soak in 40mL Zn(NO3)2 methanol (0.35 mol / L) for 1.5 hours to obtain solution B, then mix the mixture of solution B into the mixture of A and solution B, stir slightly, and react at room temperature for 18 hours. The silane hydrolyzate is composed of tetraethyl orthosilicate, ammonia water and ethanol in a volume ratio of 1:9:100, and is stirred at 50°C for 10 hours. The weight ratio of anhydrous lithium bromide to water is 3:1, and it is stirred at 5°C for 2 hours. Add microcrystalline cellulose to the silane hydrolyzate in a mass ratio of 1:11 and stir at 70°C for 15 hours. The cellulose grafted with silane is filtered out by vacuum and placed in a pressure-resistant bottle containing lithium bromide solution, with cellulose accounting for 0.4% of the total weight of the solution. Stir at room temperature for 1 hour, then ultrasonically disperse for 1 hour. Then add Ti3C2T x / ZIF-8, Ti3C2T xThe weight ratio of / ZIF-8 to cellulose was 0.1:1.1, stirred at room temperature for 1 hour, and then ultrasonically dispersed for 0.5 hours. The cellulose solution was heated to 120°C for 5 minutes, then poured into a petri dish and cooled for 12 hours to obtain a hydrogel. The hydrogel was then washed with water, ethanol, and tert-butanol in sequence, each washing for 2 hours, and then the solution was replaced and washed for 24 hours. The cellulose aerogel was obtained after freeze-drying. It was then placed in a nitrogen or argon environment, heated at 180°C for 3 hours, and then heated at 240°C for 1 hour.
[0037] (2) Preparation of triboelectric nanogenerator The modified cellulose aerogel prepared above was selected as the positive electrode of the friction nanogenerator, and the nanofiber membrane of polyvinylidene fluoride and nano-barium titanate was used as the negative electrode, with a size of 4π cm 2 , copper foil was covered on the back of the two triboelectric materials, and then fixed on acrylic plates, and the wires were connected to the upper and lower electrodes. The contact separation power generation test of the triboelectric nanogenerator was carried out with a pressure of 10N and a frequency of 4Hz.
[0038] (3) The open circuit voltage of the positive electrode of the triboelectric nanogenerator using pure cellulose nanofiber membrane without any modified materials is 58V; the open circuit voltage of the triboelectric nanogenerator using the modified cellulose-based aerogel of this embodiment as a triboelectric nanogenerator is 118V. It can be seen that the electrical output performance of the triboelectric nanogenerator of this embodiment is significantly improved. 0.3 、PM 0.5 The filtration efficiency of PM2.5, PM3 and PM4 reached 98.32%, 98.96% and 99.12% respectively. Even under the harsh conditions of high humidity of 95%RH, the filtration efficiency can be maintained above 90.2%. After 7 cycles of "test-washing", the filtration efficiency of PM2.5 was 0.3 The filtration performance is still over 92.3%. After 20 minutes of near-infrared light irradiation, the antibacterial rate of Escherichia coli and Staphylococcus aureus reached 99.25%. The device can accurately detect 5ppm NH3 and respond quickly, with a response rate of 74% to 100 ppm NH3 within 14 seconds. Even after 8 cycles of "test-washing", the bactericidal property and ammonia responsiveness remain extremely stable. By monitoring the wearer's breathing status in real time, respiratory health status can be continuously assessed. Example 3
[0039] (1) Preparation of modified cellulose aerogel 0.6 mmol Zn(NO3)2 was pre-added as a seed for crystal growth in 50 mL of 2-M (0.1 mol / L) methanol solution to obtain a mixed solution A. Ti3C2T xSoak in 30mL Zn(NO3)2 methanol (0.3 mol / L) for 1 hour to obtain solution B, then mix the mixture of solution B into the mixture of A and solution B, stir slightly, and react at room temperature for 24 hours. The silane hydrolyzate is composed of tetraethyl orthosilicate, ammonia water and ethanol in a volume ratio of 1:10:100, and is stirred at 55°C for 12 hours. The weight ratio of anhydrous lithium bromide to water is 2:1, and it is stirred at 5°C for 3 hours. Add microcrystalline cellulose to the silane hydrolyzate in a mass ratio of 1:12 and stir at 70°C for 22 hours. The cellulose grafted with silane is filtered out by vacuum and placed in a pressure-resistant bottle containing lithium bromide solution, with cellulose accounting for 1% of the total weight of the solution. Stir at room temperature for 1 hour, then ultrasonically disperse for 0.5 hours. Then add Ti3C2T x / ZIF-8, Ti3C2T x The weight ratio of / ZIF-8 to cellulose was 0.03:1.1, stirred at room temperature for 1 hour, and then ultrasonically dispersed for 1 hour. The cellulose solution was heated to 115°C for 3 minutes, then poured into a petri dish and cooled for 15 hours to obtain a hydrogel. The hydrogel was then washed with water, ethanol, and tert-butanol in sequence, each washing for 1 hour, and then the solution was replaced and washed for 24 hours. The cellulose aerogel was obtained after freeze-drying. It was then placed in a nitrogen or argon environment and heated at 200°C for 2 hours, and then heated at 230°C for 1 hour.
[0040] (2) Preparation of triboelectric nanogenerator The modified cellulose aerogel prepared above was selected as the positive electrode of the friction nanogenerator, and the nanofiber membrane of polyvinylidene fluoride and nano-barium titanate was used as the negative electrode, with a size of 4π cm 2 , copper foil was covered on the back of the two triboelectric materials, and then fixed on acrylic plates, and the wires were connected to the upper and lower electrodes. The contact separation power generation test of the triboelectric nanogenerator was carried out with a pressure of 10N and a frequency of 4Hz.
[0041] (3) The open circuit voltage of the positive electrode of the triboelectric nanogenerator using pure cellulose nanofiber membrane without any modified materials is 58V; the open circuit voltage of the triboelectric nanogenerator using the modified cellulose-based aerogel of this embodiment as a triboelectric nanogenerator is 125V. It can be seen that the electrical output performance of the triboelectric nanogenerator of this embodiment is significantly improved. 0.3 、PM 0.5 The filtration efficiency of PM2.5, PM3 and PM4 reached 98.38%, 99.03% and 99.68% respectively. Even under the harsh conditions of high humidity of 95%RH, the filtration efficiency can be maintained above 91%. After 7 cycles of "test-washing", the filtration efficiency of PM2.5 was 0.3The filtration performance is still over 92%. After 20 minutes of near-infrared light irradiation, the antibacterial rate of Escherichia coli and Staphylococcus aureus reached 99.5%. The device can accurately detect 5ppm NH3 and respond quickly, with a response rate of 75% to 100 ppm NH3 within 12 seconds. Even after 7 cycles of "test-washing", the bactericidal property and ammonia responsiveness remain extremely stable. By monitoring the wearer's breathing status in real time, respiratory health status can be continuously assessed.
[0042] Effect evaluation 1
[0043] Figure 1 The Raman spectra of all the modified materials showed a peak at 2930 cm -1 、1741 cm -1 、1415 cm -1 and 1072 cm -1 The characteristic peaks of cellulose belonging to CH stretching, CO stretching, CH bending and glycosidic stretching are retained at Figure 2 a). In the Raman spectrum of cellulose / tetraethyl orthosilicate (CT), 462 cm -1 、530 cm -1 and 784 cm -1 The characteristic peaks at 154 cm in cellulose / TES / MXene (CTM) and cellulose / TES / MXene / ZIF-8 (CTMZ) belong to O-Si-O bending vibration, Si-O-Si torsional vibration, and Si-O stretching vibration corresponding to silicon dioxide (SiO2), confirming the conversion of tetraethyl orthosilicate (TEOS) into SiO2. -1 The characteristic peaks of MXene were found at 673, 1180 and 1460 cm -1 The typical characteristic peaks at are attributed to the imidazole ring vibration, CN stretching vibration and methyl bending vibration of ZIF-8, respectively.
[0044] The XRD patterns always show a characteristic broad peak at 17°, which belongs to the (021) plane of cellulose, indicating that the modification process has not changed the basic crystal structure of cellulose ( Figure 2b). CT, CTM and CTMZ showed typical peaks belonging to SiO2 (101) and (111) planes at 20.8° and 26.2°, respectively, which confirmed the conclusion of Raman spectroscopy and Fourier transform infrared spectroscopy analysis, that is, TEOS was finally converted into SiO2 after some processing reactions. Characteristic peaks belonging to MXene were found, indicating that the material was successfully synthesized. Weak peaks belonging to ZIF-8 were found at 40-60°, but there was no corresponding ZIF-8 functional group peak in the Fourier transform infrared spectrum, which may be due to the masking effect of the two-dimensional carbon material on ZIF-8.
[0045] Figure 2 Even under extreme conditions of 95% RH, after 2 hours of continuous testing, the filtration efficiency of TENG remained above 85% ( Figure 2 ).
[0046] Figure 3 In the experiment, CTTM was irradiated with near-infrared light for 20 minutes, and the antibacterial rate against Escherichia coli reached more than 99.5% ( Figure 3 a), and CTMZ still maintains excellent and stable responsiveness to different concentrations of ammonia even after being stored at room temperature for 20 days ( Figure 3 b).
[0047] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A method for preparing a modified cellulose aerogel, characterized in that: The steps include: S11: adding a cellulose compound to a silane hydrolyzate and heating and mixing the mixture, and dispersing the separated solid in an aqueous solution of lithium bromide to obtain a mixed dispersion; the silane hydrolyzate is obtained by heating and mixing tetraethyl orthosilicate, ammonia water and ethanol at 50-75° C. for 8-20 h; S12: Add Ti3C2T x / ZIF-8 material, after mixing, heating and reacting, cooling to obtain a hydrogel; the Ti3C2T x / ZIF-8 material is obtained by mixing solution B and solution A and reacting at room temperature for 12-48 h; The solution A is obtained by mixing methanol containing dimethyl imidazole and zinc nitrate; the solution B is obtained by mixing Ti3C2T x It is obtained by adding to methanol containing zinc nitrate; S13: washing the hydrogel, freeze-drying it, and heat-treating it to obtain the modified cellulose aerogel.
2. The preparation method according to claim 1, characterized in that The cellulose compound is selected from microcrystalline cellulose, nanocellulose or cellulose; the mass ratio of the cellulose compound to the silane hydrolyzate is 1:5-15.
3. The preparation method according to claim 1, characterized in that: In the step S11, the cellulose compound and the silane hydrolyzate are heated and mixed at a temperature of 50-70° C. for 5-24 h.
4. The preparation method according to claim 1, characterized in that: The aqueous solution of lithium bromide has a weight ratio of lithium bromide to water of 2:1-3 and is stirred at 0-15°C for 0.5-5 h.
5. The preparation method according to claim 1, characterized in that: In the silane hydrolyzate, the volume ratio of tetraethyl orthosilicate, ammonia water and ethanol is 0.8-1.4:9-14:92-108.
6. The preparation method according to claim 1, characterized in that: In step S12, Ti3C2T x The mass ratio of the cellulose compound in the / ZIF-8 material and the mixed dispersion is 0.02-0.3:0.8-1.
2.
7. The preparation method according to claim 1, characterized in that: In step S12, the heating reaction temperature is 95-140° C., the time is 1-10 min, and the cooling is 6-24 h.
8. The preparation method according to claim 1, characterized in that: In the step S13, the heat treatment method is: in a protective atmosphere, heating the freeze-dried hydrogel at 150-200° C. for 0.5-4 h, and then heating at 220-260° C. for 0.5-4 h.
9. A modified cellulose aerogel prepared by the preparation method according to any one of claims 1 to 8.
10. A friction nanogenerator, characterized in that: The modified cellulose aerogel according to claim 9 is used as the positive electrode material.
Citation Information
Patent Citations
Biomass carbon aerogel of hollow hierarchical core-shell structure as well as preparation method and application of biomass carbon aerogel
CN108837798A
Carbon aerogel with ultra-high linear sensitivity and preparation and application thereof in sensor
CN109095449A
Preparation method and application of super-hydrophobic MXene-based / cellulose composite aerogel
CN114288953A
Preparation method of composite porous aerogel material
CN114914097A
Moisture-resistant cellulose triboelectric material for motion sensing and preparation method thereof
CN117281506A